THE ANALYSIS OF LEXICAL COHESION IN NATIONAL COLUMN AS FOUND IN THE JAKARTA POST NEWSPAPER - Nur Habibah; Urip Sulistiyo (Universitas Jambi, 2018)
This thesis discussed about the analysis of lexical cohesion in National column in the Jakarta Post newspaper. It aimed at finding out the type of lexical cohesion in National column in the Jakarta Post newspaper, knowing how is the use of lexical cohesion in national column in the Jakarta Post newspaper and knowing what is the dominant item of lexical cohesion in national column in the Jakarta Post newspaper. This research used semantics theory by Noam Chomsky. The data were taken from national column in the Jakarta Post newspaper 2015. In doing analyses, the researchers used content analysis technique by Klaus Krindrauft. From the analysis, the researchers found that there were five types of lexical cohesion such as; 107 of repetitions , 48 of synonymy, 13 of antonyms, 50 of hyponymy and 30 of hypernymy. Most of lexicon was found in simple past. The using of lexical cohesion on national column in the Jakarta Post newspaper is good but there are some of repetitions that can be changed by pronouns. Another finding was the dominant type of lexical cohesion in national column is Repetition.